2004
DOI: 10.1590/s0102-76382004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Relação anatômica entre a porção posterior do ânulo mitral e as artérias coronárias: implicações no tratamento cirúrgico

Abstract: Objective: This work aimed at analyzing the anatomical relationship among the mitral annulus, the circumflex artery and the posterior left ventricular artery, correlating the distance among these structures to the pattern of coronary network dominance.Method: Eighty-five human hearts, previously preserved in 10% formaldehyde solution, were studied. The coronary network dominance pattern was initially evaluated. Next, atriotomy and left ventriculotomy in the posterior wall of the heart were performed, starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Virmani et al found an association between injury and the spatial relationship between the left coronary artery and MV annulus, further stating that the risk of injury is higher in patients with left coronary dominance/codominance (average distance of Cx from the mitral annulus was 4.1 mm for left dominance, 5.5 mm for codominance, and 8.4 mm for right dominance) (5). On the other hand, Pessa et al did not find this association, but their study included only two patients with left coronary dominance (6). Our case supports the association of left coronary dominance with a higher likelihood of Cx injury after MV repair (6).…”
Section: Discussionmentioning
confidence: 96%
“…Virmani et al found an association between injury and the spatial relationship between the left coronary artery and MV annulus, further stating that the risk of injury is higher in patients with left coronary dominance/codominance (average distance of Cx from the mitral annulus was 4.1 mm for left dominance, 5.5 mm for codominance, and 8.4 mm for right dominance) (5). On the other hand, Pessa et al did not find this association, but their study included only two patients with left coronary dominance (6). Our case supports the association of left coronary dominance with a higher likelihood of Cx injury after MV repair (6).…”
Section: Discussionmentioning
confidence: 96%